APPROACHES TO THE NATURE OF BIOLOGICAL ACTIVITIES AND THEIR CLASSIFICATION - Salima Akhmetova (Scholar Express Journals, 2024)
The article discusses scientific research conducted in foreign countries on the assessment of biological assets. The possibilities of using foreign experience in the practice of farms operating in our republic are shown
Keywords: biological assets; agricultural products; valuation